1997
DOI: 10.1111/j.1524-4725.1997.tb00462.x
|View full text |Cite
|
Sign up to set email alerts
|

Infusion Rates and Levels of Premedication in Tumescent Liposuction

Abstract: Infusion rates for tumescent anesthesia can be increased of greater amounts of premedication are given. However, this must be balanced against the safety of the premedication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…In many cases, the procedures can be performed under local anesthesia alone, without any sedation. 8 The maximum dose of lidocaine that can safely be employed (50–60 mg/kg) automatically limits the size of the liposuction case. The safety profile of this form of liposuction has been demonstrated over and over in a series of studies.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, the procedures can be performed under local anesthesia alone, without any sedation. 8 The maximum dose of lidocaine that can safely be employed (50–60 mg/kg) automatically limits the size of the liposuction case. The safety profile of this form of liposuction has been demonstrated over and over in a series of studies.…”
Section: Discussionmentioning
confidence: 99%
“…Further, blood loss cannot be calculated from blood in the aspirate, 24 and the concentration of epinephrine affects lidocaine absorption. 25 Other issues of controversy associated with liposuction include infusion rates and use of premedication, 26 the efficacy of external ultrasound-assisted liposuction, internal ultrasonic-assisted liposuction or external ultrasound after liposuction, [27][28][29][30] and use of postoperative garments/length of postoperative compression. 31,32…”
mentioning
confidence: 99%
“…Some studies examine levels after infiltration is complete 8 or measure the first level 3–4 hours after infiltration. 1,9 Rapid delivery of tumescent solution generally requires more sedation to relieve discomfort, 5 therefore patients may be less able to report early subjective signs of toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have underscored the importance of the infiltration period. Hanke et al's 5 study showed that dermatologic surgeons are using infiltration pumps that now allow increasingly rapid rates of infiltration of tumescent anesthesia, providing that adequate preoperative medication is given to reduce the pain of infiltration. In addition, intravascular injection of lidocaine during infiltration of a tumescent solution of lidocaine has been reported during phlebectomy when infusion was performed with a nonaspirating injection syringe.…”
mentioning
confidence: 99%